Carbon tax revenue could fund a $2,000/year dividend to offset household costs. - Barthes (Isonomia, 2025)
Carbon tax revenue could fund a $2,000/year dividend to offset household costs.
iso-id: iso:argument:qi94dhu7; sha256: sha256:5e43089713cdf31377d03e9eff1ea43a92732d9a63677c612e2350233bd899ea